Inside BAR (The Biblical archaeology review, 1983)
An Israeli soldier named Ofer Broshi recently found by accident a partially buried ancient bronze figurine of a bull. With Broshi’s help, archaeologist Amihai Mazar was able to locate and later excavate the early Israelite cult site in northern Samaria where the bull had been buried. In "Bronze Bull Found in Israelite ‘High Place’s […]